Life forms protectable as subjects of US patents--microbes to animals (perhaps) - Hodgins, D S (Applied biochemistry and biotechnology, 1987)
Scientists, businessmen, universities, and industries with fundamental or peripheral interests in technology as applied to life processes will be keenly interested in recent US Patent Office decisions. These decisions indicate that new higher life forms, animal or plant, are proper subjects of patents if they are not naturally occurring (and are not human, in the case of animals). In contrast to plants and other organisms, genetically modified animals have had no mode of protection as intellectual property except possibly as trade secrets or utility patents. The Ex parte Allen decision, reached by the Patent Office Board of Appeals and Interferences, directly addressed the issue of animal patentability in view of the broad reading of 35 U.S.C. section 101 by the US Supreme Court in the Chakrabarty decision. The subject invention concerned polyploid oysters. Claims directed toward polyploid oysters produced by a particular process were rejected under 35 U.S.C. section 103 and section 101. The Board, reversing the 35 U.S.C. section 101-based rejection in view of the Chakrabarty decision, indicated that the claimed polyploid oysters were non-naturally occurring manufactures or compositions of matter within the confines of patentable subject matter under 35 U.S.C. section 101. A similar decision affecting the patentable status of plants or segments thereof had previously been reached by the Patent and Trademark Office in the case of Ex parte Hibberd, 227 U.S.P.Q. 443 (Bd. Pat. App. 1985). The Hibberd utility patent application concerned "genetically engineered" maize which had high levels of the tryptophan.